(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2021)
Recent advances in materials engineering have given rise to a new class of materials known as active materials. These materials when used appropriately can aid in development of smart structural systems. This research presents the smart composite beam study in experimental and numerical by ANSYS V.15. In the present research, shape memory alloy NiTinol wire as fiber was used with a linear low density polyethylene (LLDPE) as host matrix. Nitinol wire high temperature is about 80°C±10°C full annealed, (2 mm) with a straight shape, black color, it consists of (Ni-55%, H-0.001%, O-0.05%, N-0.001%, C-0.05%, Ti-Balance). The model consists of four NiTinol wires, each one with 180 mm length and 2 mm diameter, the distance between them is about 10 mm. In the experiment, the model was subjected to a bending load with speed 500 mm/min and displacement 30 mm. After unloading, the composite backed upward (spring-back) by a displacement about 13 mm and stopped. But, the spring back in finite element modeling was about 12.5 mm, the error percentage between the experimental and finite elements results is about 3.8%. Recovery stress is sufficient to return the composite beam to the original shape and position. The factors play the important role in the recovery composite beam are recovery stress, rigidity of host matrix, interfacial bonded force, pre-strain and activation temperature. The temperatures distribution is same on the surface of smart composite beam model in the middle line in both cases, finite elements modeling and experimental work. The pre-strain 4% is enough to recover the composite model after activation. The chosen polymeric host is very significant, because through activation of NiTinol wire, the host material becomes flexible.